The Built-in Flexibility of Income and Consumption Taxes in New Zealand - John Creedy; Norman Gemmell (New Zealand Government, The Treasury, 2003)
This paper provides estimates of individual and aggregate revenue elasticities of income and consumption taxes in New Zealand, based on the 2001 tax structure and expenditure patterns. Using analytical expressions for revenue elasticities at the individual and aggregate levels, together with a simulated income distribution, values for New Zealand were obtained. Results using equi-proportional income changes suggest that the aggregate income and consumption tax revenue elasticities are both fairly constant as mean income increases, at around 1.3 and 0.95 respectively. This latter estimate assumes that increases in disposable income are accompanied by approximately proportional increases in total expenditure. If there is a tendency for the savings proportion to increase as disposable income increases, a somewhat lower total consumption tax revenue elasticity, of around 0.9, is obtained for 2001 income levels. However, non-equiproportional income changes are more realistic. Allowing for regression towards the geometric mean income reduces these elasticities, giving an elasticity for income and consumption taxes combined that is only slightly above unity. Examination of the tax-share weighted expenditure elasticities for various goods also revealed that, despite the adoption of a broad based GST at a uniform rate in New Zealand, the persistence of various excises has an important effect on the overall consumption tax revenue elasticity, especially for individuals at relatively low income levels.
Keywords: H60; H71; 330; Tax Revenue; Elasticity; Budget Shares